The The AI, Hedonism, Impulsive Buying, Self-Control, and TikTok PayLater Loans - Wahyu Dianto; Risal Rinofah; Pristin Prima Sari (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2026)
This study aims to examine and analyze (1) the effect of artificial intelligence on loan decisions using TikTok Paylater, (2) the effect of hedonistic lifestyle on loan decisions using TikTok Paylater (3) The effect of impulsive buying on loan decisions using TikTok Paylater (4) The effect of artificial intelligence on loan decisions using TikTok Paylater through self-control (5) The effect of hedonistic lifestyle on loan decisions using TikTok Paylater through self-control (6) The Influence of Impulsive Purchasing on Loan Decisions Using TikTok Paylater Through Self-Control, and (7) The Influence of Self-Control on Loan Decisions Using TikTok Paylater. The sample in this study consisted of 110 Gen Z respondents in Yogyakarta who were active TikTok Shop users and had made at least one transaction using TikTok Paylater in the last month. Data collection was conducted by distributing questionnaires through social media, and the sampling technique used was purposive sampling. This study used the Outer Model analysis technique, Model Fit Test, and Inner Model Analysis. The analysis software used was SmartPLS 4.1.0.9. The results of the study show that (1) there is a positive and significant effect between the Artificial Intelligence variable and the decision to borrow using TikTok Paylater (2) there is no positive and significant effect of the Hedonistic Lifestyle variable on the decision to borrow using TikTok Paylater (3) there is no positive and significant effect of the Impulsive Purchasing variable on the decision to borrow using TikTok Paylater (4) There is no positive effect of the Artificial Intelligence variable on the decision to borrow using TikTok Paylater through Self-Control (5) There is no positive and significant effect of the Hedonistic Lifestyle variable on the decision to borrow using TikTok Paylater through Self-Control (6) There is no positive and significant effect of the Impulsive Purchasing variable on Loan Decisions Using TikTok Paylater through Self-Control (7) There is no positive and significant effect of the Self-Control variable on Loan Decisions Using TikTok Paylater.